Perilaku Pemilih Gen Z Pada Pemilihan Presiden Tahun 2024: Studi Terhadap Perilaku Mahasiswi Unimed Pada Pemilihan Presiden 2024 - Sarah Lestari Tampubolon; Tri Bayu Armanda; Depi Yohana Manurung; Unedo Sinaga; Limra Nababan; Joy Prana Bangun (Lembaga Pengembangan Kinerja Dosen, 2024)
Elections are an integral part of the Indonesian political system itself. Regular elections are held every five years during the leadership period. Indonesia adheres to a democratic system in which every citizen has the right to give their rights and votes to government officials or the highest state institutions and elections are part of the democratic system itself. We held a democratic party last February, we encountered many unique things during the election, especially in the younger generation or what is now called Gen-Z. In this research, our group used qualitative research methods. Qualitative research is research carried out directly in the field to obtain information or factual data that occurs in the field, assisted by several sources of informants who can strengthen our research. This research was carried out with the aim of finding out how participation was and how far Gen-Z understood the previous elections, whether there were any pros or cons during the leadership election. Therefore, let's discuss further in the discussion regarding Gen-Z participation in elections.